Financing Pharmaceutical Innovation : How Much Should Poor Countries Contribute? - Jack, William; Lanjouw, Jean O. (Published by Oxford University Press on behalf of the World Bank, 2014)
A public economics framework is used to consider how pharmaceuticals should be priced when at least some of the research and development incentive comes from sales revenues. Familiar techniques of public finance are used to relax some of the restrictions implied in the standard use of Ramsey pricing. Under the more general model, poor countries should not necessarily cover even their own marginal costs, and the pricing structure is not related to that which will be chosen by a monopolist in a simple way. This framework is then used to examine ongoing debates regarding the international patent system as embodied in the world trade organization's agreement on trade-related aspects of intellectual property rights.